Teori Munasabah dan Aplikasinya Dalam Al Qur’an - Ahmad Fauzul Adlim (Al Furqan: Jurnal Ilmu Al Quran dan Tafsir, 2018)
In the study of Qur'anic and tafsir, munasabah science is an inseparable part to be discussed. It is a tool for understanding the content of the Qur'an. The variety of discussions that exist in the Qur'an increasingly positioned the importance of munasabah science. In this regard, M. Quraish Shihab, a prominent Indonesian exegete, analogized the variety of Qur'anic discussions in a letter and its relation to one letter to another (munasabah), like an unknown pearl necklace in which the tip and the hilt are. The existence of knowledge about Munasabah in the Qur'an is based on an opinion that the composition of the verses, the order of sentences and letters in the Qur'an are arranged by tauqifi not ijtihadi. Therefore the placement of verses, sentences and letters are based on tauqifi, that's what we want to find, because behind the placement of verses and letters like that of course there is a wisdom contained in it. On the contrary, the argument that the composition of the verses, the order of sentences and letters in the Qur'an in a stratified manner clearly will undermine the munasabah theory in the Qur'an. As al-Suyuthi, Nasr Hamid Abu Zaid reveals that Munasabah are of a general nature and some are specific, some are rational, perceptive, or imaginative. This according to Abu Zaid shows that the relationships or Munasabah-Munasabah are possibilities. These possibilities should be disclosed and determined on each part of the text by commentators. Expressing the relationships between verses and verses and between letters and letters does not mean explaining relationships that exist in inherently in the text, but making connections between the commentators' mind and the text. It is through this relationship that the relationship between the passages of the text can be expressed